Researching practitioner experiences through autoethnography: Embodying social policy, exploring emotional landscapes. (March 2019) - Henderson, Elizabeth
This article highlights autoethnography as an arts-based methodology in early years research, giving consideration to its challenges and critics as well as the power of its application to elicit voices in a way that other methodologies do not. It embraces and models autoethnography through sharing a performative autoethnographic narrative of one practitioner's experiences as she grapples with implementing child protection/safeguarding policies, exploring the embodiment of social policy and the consequent dissonance in emotions that lead to a disruption in identity. It asks, 'What do policy imperatives actually feel like in practice and how might autoethnography, as an arts-based methodology, afford researchers a way to illustrate this?' Challenging the perception of what it means to be an early years practitioner, through an evocative and provocative narrative, this article foregrounds the need to overcome the historical silencing of practitioner's voices while illustrating the value of autoethnographic research in helping to reveal the multiple layers of power and dissonance in a pedagogical space such as a nursery. Adopting a critical stance, to avert challenges of solipsism and to further extend the debate around practitioner identity, the performative autoethnographic narrative is later reflected within the wider context of relevant literature. Finally, consideration is given to the question of why autoethnographic research is under-represented in the early years field, particularly at a time when it is prudent to create a wider epistemological base to extend the discourse around what support practitioners need to help them fulfil their vital role in children's lives.